2019
DOI: 10.3390/genes10120975
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phenotypic Variations and Correlation among Seed Composition Traits in Mutagenized Soybean Populations

Abstract: Soybean [Glycine max (L.) Merr.] seed is a valuable source of protein and oil worldwide. Traditionally, the natural variations were heavily used in conventional soybean breeding programs to select desired traits. However, traditional plant breeding is encumbered with low frequencies of spontaneous mutations. In mutation breeding, genetic variations from induced mutations provide abundant sources of alterations in important soybean traits; this facilitated the development of soybean germplasm with modified seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
11
0
3
Order By: Relevance
“…In current study, oil content showed positive correlation with the C18:1 n-9c, but negatively with C16:0, C18:0 and C18:2 n-6c. Our results partly correspond to those determined in Theobroma cacao by Mustiga et al [45], and in soybean by Zhou et al [46]. Such a contradiction Fig.…”
Section: Correlation Between Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…In current study, oil content showed positive correlation with the C18:1 n-9c, but negatively with C16:0, C18:0 and C18:2 n-6c. Our results partly correspond to those determined in Theobroma cacao by Mustiga et al [45], and in soybean by Zhou et al [46]. Such a contradiction Fig.…”
Section: Correlation Between Variablessupporting
confidence: 92%
“…2). This means that in some peach kernel`s oil, the palmitic acid is not only converted into stearic acid and that stearic acid is not only dependent on palmitic acid, and vice versa [46]. Mustiga et al [45] also found significant negative correlations between palmitic acid and stearic acid in cacao (Theobroma cacao L.) beans, while Islam et al [47] found positive correlation between those two saturated fatty acids in rapeseed (Brassica napus) and mustard (B. juncea).…”
Section: Correlation Between Variablesmentioning
confidence: 99%
“…After domestication, cultivated soybean exhibit diverse traits from wild soybean, and 100-SW for G. max is almost 6–7 fold greater than Glycine soja [ 4 , 5 , 6 ]. Seed weight (SW) is a quantitatively inherited trait and controlled by multiple genes, with various main and epistatic effects [ 2 , 7 , 8 , 9 ], and significantly influenced by the growing environmental conditions. Due to the quantitative nature, it is difficult to develop superior cultivars by traditional breeding.…”
Section: Introductionmentioning
confidence: 99%
“…For EMS mutant lines, a five-seed sample taken from each M3 mutant line was placed in an envelope and manually crushed with a hammer. Fatty acid extraction procedure was carried out as previously described [ 42 ]. Five major fatty acid contents were measured from selected according to the two-step methylation procedure as described earlier [ 43 ].…”
Section: Methodsmentioning
confidence: 99%